Identifying developmental language disorder in bilingual children from diverse linguistic backgrounds - Li el, N.; Williams, C.; Kane, Robert (2018)
© 2018, The Speech Pathology Association of Australia Limited. Purpose: To investigate an assessment approach that incorporates a parent questionnaire (ALDeQ) and two language processing tasks (nonword repetition [NWR] and recalling sentences [RS]) administered in English to differentiate bilingual children with Developmental Language Disorder (DLD) from typically developing (TD) bilingual children. Method: Participants were 42 typically developing bilingual children (biTD) and 19 bilingual children with DLD (biDLD). Groups were matched for age (M = 5;10) socioeconomic status (M = 1,023 SEIFA) and length of exposure to English (M = 33.4 months). Children were given a NWR and RS task. Parents completed the ALDeQ. Result: BiDLD had significantly (p < 0.005) lower average scores than biTD on all three assessment tools. The ALDeQ provided the highest diagnostic accuracy (100% sensitivity, 95.2% specificity, area under the curve [AUC] = 0.991). Two other combinations also provided good diagnostic accuracy (above 80% sensitivity and 80% specificity): combination of ALDeQ and NWR; scores below the cut-offline on any combination of assessment tools. Conclusion: Correct identification of DLD among bilingual children using an all English approach is possible. This approach has the potential to provide a practical and evidence-based solution for English speaking speech-language pathologists (SLPs) working with bilingual children.